Performance of adaptively loaded OFDM under Rayleigh fading with diversity combining - Canpolat, B.; Tanik, Y. (IEEE 54th Vehicular Technology Conference. VTC Fall 2001. Proceedings (Cat. No.01CH37211), 2001)
In this study, we investigate the performance of adaptively loaded OFDM (orthogonal frequency division multiplexing) under Rayleigh fading with ideal maximal ratio diversity combining (MRC). We consider two approaches for adaptive loading: maximization of throughput subject to total transmit power and subcarrier error rate constraints and minimization of subcarrier error rate subject to total transmit power and target bit rate constraints. We demonstrate the performance improvement of adaptive loading over fixed loading in both cases. A tight lower bound on the average spectral efficiency of the throughput maximizing adaptive loading method under Rayleigh fading with diversity combining is obtained. For the error rate minimization approach, an optimum integer bit loading algorithm is presented which is computationally simpler than the optimum Hughes-Hartogs algorithm.